2015
DOI: 10.1186/s12879-015-1185-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic differentiation of lung nodules caused by mycobacteria and lung cancer: a case–control study

Abstract: BackgroundLung nodules caused by mycobacteria can resemble lung cancer on chest imaging. The advent of lung cancer screening with low-dose Computed Tomography is accompanied by high false-positive rates, making it necessary to establish criteria to differentiate malignant from benign nodules.MethodsWe conducted a retrospective case–control study of 52 patients with mycobacterial lung nodules and 139 patients with lung cancer, diagnosed between 2010 and 2012. We compared clinical and radiographic characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The present study showed that the means diameter and thickness of malignant cavitary lesion were significantly higher than benign cavitary lesions (p<0.001). This finding coincides with the results of Figueroa et al 15 18 . Malignant pulmonary cavitation characterized by irregular or round appearance with discrepancy in wall thickness.…”
Section: Discussionsupporting
confidence: 94%
“…The present study showed that the means diameter and thickness of malignant cavitary lesion were significantly higher than benign cavitary lesions (p<0.001). This finding coincides with the results of Figueroa et al 15 18 . Malignant pulmonary cavitation characterized by irregular or round appearance with discrepancy in wall thickness.…”
Section: Discussionsupporting
confidence: 94%
“…Using computed tomography (CT) to screen for lung cancer is highly recommended but frequently causes a high false‐positive rate of around 70% . Considering the high frequency of benign lesions, differentiation between benign and malignant lesions before invasive biopsy is becoming increasingly important …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Considering the high frequency of benign lesions, differentiation between benign and malignant lesions before invasive biopsy is becoming increasingly important. 10,11 Many radiological features of pulmonary infections have been demonstrated in CT images, such as lobar, segmental, or alveolar consolidation with blurred margins, ground glass opacities, centrilobular nodules, the tree-in-bud sign, reticulation, cavitation, wedgeshaped consolidation, bronchiectasis, necrotic lymphadenopathy, smooth inner wall of cavitation, calcification, among others. [12][13][14] However, malignancies can share similar radiological patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the differentiation between benign and malignant lesions using 18 F-FDG PET/CT have been inconclusive. Figueroa et al showed that the specificity of 18 F-FDG PET/CT is not sufficient to differentiate between lung nodules caused by NTM and cancer, as an increased maximum standardized uptake value (SUV max) is obtained in both types of lesion [16]. According to the authors, an SUV max value ≥ 16 may be more specific for cancer diagnosis as such values were not observed in NTM lesions.…”
Section: Discussionmentioning
confidence: 99%